2012
DOI: 10.1016/j.devcel.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

ALIX Is a Lys63-Specific Polyubiquitin Binding Protein that Functions in Retrovirus Budding

Abstract: SUMMARY The diversity of ubiquitin (Ub)-dependent signaling is attributed to the ability of this small protein to form different types of covalently linked polyUb chains and to the existence of Ub binding proteins that interpret this molecular syntax. We used affinity capture/mass spectrometry to identify ALIX, a component of the ESCRT pathway, that has not been previously reported to possess a Ub binding domain. We report that the V domain of ALIX binds directly and selectively to K63-linked polyUb chains, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 48 publications
(71 reference statements)
5
70
0
Order By: Relevance
“…8). This finding is consistent with several studies that suggested that ubiquitin is involved in viral budding: (i) proteasome inhibitor treatments block the budding of paramyxoviruses, including PIV5, NiV, and SeV (26,31,58); (ii) potential ubiquitination of the MeV M protein has been observed in cells expressing the M protein together with HA-Ub (38); and (iii) ESCRT factors such as ALIX can bind to ubiquitin and enhance viral budding (59,60).…”
Section: Discussionsupporting
confidence: 79%
“…8). This finding is consistent with several studies that suggested that ubiquitin is involved in viral budding: (i) proteasome inhibitor treatments block the budding of paramyxoviruses, including PIV5, NiV, and SeV (26,31,58); (ii) potential ubiquitination of the MeV M protein has been observed in cells expressing the M protein together with HA-Ub (38); and (iii) ESCRT factors such as ALIX can bind to ubiquitin and enhance viral budding (59,60).…”
Section: Discussionsupporting
confidence: 79%
“…ALIX is a conserved protein in eukaryotes that was implicated in cytokinesis, ILV, and exosome biogenesis and endosomal sorting (28). Human ALIX was also suggested to play a role during viral infection and budding (29)(30)(31). Mammalian ALIX, yeast Bro1p, and their Arabidopsis homolog were all shown to interact with ESCRT-III via the charged multivesicular body protein 4/sucrose nonfermenting 7p (CHMP4/Snf7p) subunit (32)(33)(34)(35).…”
Section: Significancementioning
confidence: 99%
“…The V-domain of both Bro1p and human ALIX was shown to mediate the interaction with ubiquitin in intracellular trafficking (29,31,44). Because the amino acid sequence homology in the Arabidopsis ALIX V-domain is relatively moderate (25% amino acid identity with human ALIX and 17% with Bro1p), we tested whether it could bind ubiquitin.…”
Section: Alix Binds Ubiquitin and Is Involved In Ubiquitin-dependent mentioning
confidence: 99%
“…(1) it lacks the ability to recognize ubiquitin directly, although recent reports indicate ES-CRT-III-interacting protein Bro1/Alix (ALG2-interacting protein X) can directly bind ubiquitin (Dowlatshahi et al 2012); (2) it displays no lipid specificity for PtdIns(3)P, implying why it can directly function in membrane remodeling at both endosomes as well as the plasma membrane; and (3) ESCRT-III does not form a stable complex, but rather assembles transiently during membrane sculpting and fission events. ESCRT-III is additionally unique because this membrane-remodeling machine induces invaginations that protrude away from the cell cytoplasm.…”
mentioning
confidence: 99%